The Influence of Rootstock on the Rooting Pattern of the Grapevine - SWANEPOEL, J. J.; SOUTHEY, J. M. (South African Journal of Enology and Viticulture, 2017)
The rooting pattern of rootstocks grafted with Chenin blanc, on an Oakleaf soil with minimwn restrictions to root penetration, was investigated. Both root density and distribution were affected by rootstock. Under conditions of intensive irrigation and high potential soil, the best colonisation and utilisation of the available soil volume was obtained with Berlandieri 13/5, 101-14 Mgt and 1103 Paulsen while 140 Ruggeri and US 12-6-8 performed poorly as regards their subterranean growth. This was also reflected in the above ground performance.